الظروف الميتيورولوجية وإنتاجية العنب vitis vinifera في سورية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
دلت نتائج الدراسة وجود تراجع  معدل إنتاجية شجرة الكرمة في حلب وحمص والسويداء بلغ على التوالي (2.0808 - ، 0.1071 - ، 2.488 - ) وتزايد في حماه بلغ (0.3648) كغ/ شجرة  . تفاوتت التراكمات الحرارية الفعالة خلال موسم نمو الكرمة في كل منطقة من المناطق الأربع وبقيم بلغت (2863.6 ، 2793.8 ، 2539.8 ، 2212.4  درجة نمو يومية)  في حماه ، حلب ، حمص ،السويداء على التوالي. أيضاً وضحت نتائج معادلات اتجاه التغير (الترند) وجود زيادة في التراكمات الحرارية الفعالة خلال موسم نمو العنب في حلب وحماه وحمص وتراجع في السويداء . أخيراً ربطت معادلات الانحدار المتعدد بين إنتاجية الكرمة وأهم أربع عناصر مناخية مؤثرة خلال مراحل نمو العنب في كل منطقة من المناطق الأربع المدروسة .The results of this study clearly indicate that the average of vitis vinifera productivity has decreased during the research period in Aleppo, Homs, and Sweida by (-2.0808,-0.1071,-2.488 kg/tree), respectively , and  has increased in Hama by (0.3648 kg/tree). The effective thermal accumulation during the growing season of vitis vinifera in each area reaches ( 2863.6,2793.8,2539.8,2212.4 G.D.D.) in Hama, Aleppo, Homs and Sweida, respectively. The results of Trend  have demonstrated an increase in the effective thermal accumulations during growing season of the grapes in Aleppo, Hama, and Homs, and a decrease in Sweida. Finally, the multi-slope equation has attributed the productivity of grapes to the  four most  important climatic conditions affecting grapes  during  the growing stages in each of the four areas.